he effect of the L.B.D strategy on the achievement of primary school students in mathemat (Journal of the College of Basic Education, 2024)
The aim of the research is to identify ( the effect of the L.B.D strategy on the achievement of primary school students in mathematics ) . The research sample was chosen intentionally and represented fifth-grade primary school students at (Nour Al-Marefa Primary School for Boys ) . affiliated with the General Directorate of Rusafa Education 2 , for the first semester of the year ( 2023 - 2024 ) , and the researcher adopted the experimental method with partial control through the post – test , and the research sample consisted of (61) students , and by random selection , they were distributed into two groups , one of which was Division (A) , representing the experimental group with (31) students taught according to the L.B.D strategy , and the second , Division (C) , representing the control group with (30) students taught according to the usual method , and the researcher studied The two groups themselves .. The two groups were rewarded on variables (chronological age calculated in months , previous mathematics achievement , intelligence test , and previous mathematics knowledge test ) . The research tool represented by the achievement test was built , consisting of (20) multiple-choice items with four alternatives . After the end of the experiment , the test was applied to the two research groups , and using appropriate statistical methods , the results showed (there is a statistically significant difference at the level of significance (0.05) between the average scores of the experimental group students who were taught according to the L.B.D strategy and the average scores of the control group students who were studied according to the normal method in the test , achievement , for the benefit of the experimental group ) .In light of the results, several conclusions were reached, including :: Teaching mathematics using the L.B.D strategy has an impact on the achievement of students in the experimental groupA number of recommendations and proposals were made, the most important of which are : Encouraging and urging mathematics teachers at all academic levels to use the L.B.D strategy, in addition to conducting in-service training courses on applying the strategy and how to employ it in teaching mathematics .The most important proposals : Conducting studies similar to the current study on universities and secondary schools, as well as conducting studies to determine the impact of the L.B.D strategy on other variables .